Dynamic Changes in the Global MicroRNAome and Transcriptome Identify Key Nodes Associated With Ovarian Development in Chickens - Wang, Wenwen; Wu, Keliang; Jia, Meiting; Sun, Shuhong; Kang, Li; Zhang, Qin; Tang, Hui (Frontiers in Genetics, 2018)
Gaining insight into the gene expression patterns during ovarian follicle development will benefit the improvement of the laying performance as well as the better understanding of avian reproductive physiology. To better understand the molecular regulation of ovarian development, a systematic profiling of miRNAs and mRNAs from the ovary at four key stages of development (at ages of 60 days (A), 100 days (B), 140 days-not yet laying eggs (C) and 140 days-just starting to lay eggs (D)) were performed. A total of 73 differentially expressed miRNAs (DEMs) (14 for B vs. A, 8 for C vs. B and 51 for D vs. C, respectively) and 2596 differentially expressed genes (DEGs) (51 for B vs. A, 20 for C vs. B and 2579 for D vs. C, respectively) between the four consecutive stages were identified. At the same time, 174 DEMs (22 for C vs. A, 74 for D vs. A and 78 for D vs. B, respectively) and 3205 DEGs (118 for C vs. A, 2284 for D vs. A and 2882 for D vs. B, respectively) between nonconsecutive stageswere also identified. Among these DEGs, some are involved in the Wnt and TGF-beta signaling pathways, known to affect ovarian development and ovulation. An integrative analysis of miRNA and mRNA profiling data identified 3166 putative miRNA-mRNA regulatory pairs containing 84 DEMs and 1047 DEGs. Functional annotation of the networks provides strong evidence that the miRNA regulatory networks may play vital roles in ovarian development and ovulation. Ten differentially expressed miRNAs and ten genes were validated by real-time quantitative PCR. The miRNA-mRNA pairs gga-miR-200a-3p-SFRP4, gga-miR-101-3p-BMP5, gga-miR-32-5p-FZD4 and gga-miR-458b-5p-CTNNB1 were identified as new candidate interaction pairs potentially associated with ovarian development.